The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.energyfuels.0c01590
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Polymeric Relative Permeability Modifier Adsorption onto Carbonate Rocks

Abstract: Relative permeability modifiers (RPMs) are chemicals that can be injected into a reservoir to change its fluid/gas transport characteristics. For example, RPMs can reduce the relative permeability to water in a subterranean reservoir while having minimal impact on hydrocarbon production. Most commercially available RPMs are specifically designed for silica surfaces which are dominant in sandstone reservoirs. However, the concentration of silica in carbonate rocks is very low and many of these RPMs are unsuitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Generally, the concentration of uncross-linked polymers used in sandstone reservoirs is less than 0.3 wt %; higher concentrations of polymer can lead to undesirably large reductions in the permeability for both oil and brine. , Given that carbonate core samples contain narrow pores with a small average pore radius and generally weak pore connectivity compared to typical sandstone core samples of similar permeability/porosity, the polymer concentration will likely need to be less. The RPM formulation we used in a previous study had a higher concentration of a polymer of 0.6 wt % (and correspondingly higher amounts of formaldehyde, sodium silicate, and APTES) and a higher viscosity; however, there was a concern that 0.6 wt % might cause a blockage of high-permeability channels in the carbonate core sample when PAM-co-AA is immobilized onto the pore walls after the RPM flooding. As a result, for all the RPM formulations used in this study, a polymer concentration less than 0.3 wt % was used.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the concentration of uncross-linked polymers used in sandstone reservoirs is less than 0.3 wt %; higher concentrations of polymer can lead to undesirably large reductions in the permeability for both oil and brine. , Given that carbonate core samples contain narrow pores with a small average pore radius and generally weak pore connectivity compared to typical sandstone core samples of similar permeability/porosity, the polymer concentration will likely need to be less. The RPM formulation we used in a previous study had a higher concentration of a polymer of 0.6 wt % (and correspondingly higher amounts of formaldehyde, sodium silicate, and APTES) and a higher viscosity; however, there was a concern that 0.6 wt % might cause a blockage of high-permeability channels in the carbonate core sample when PAM-co-AA is immobilized onto the pore walls after the RPM flooding. As a result, for all the RPM formulations used in this study, a polymer concentration less than 0.3 wt % was used.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regardless of the precise mechanism, to date, very little research has been done utilizing RPM formulations in carbonate rocks. , This can be attributed to the significant differences (i.e., mineral compositions, pore structure, and permeability characteristics) between carbonate rocks and sandstones. Aiming at making a new RPM applied in carbonate rocks, based on our previous studies, , we have shown that we can efficiently functionalize/immobilize polyacrylamides onto the pore surface of carbonate rocks. ,, In our previous study, sodium silicate was used to functionalize the carbonate surface with silicate groups, and then, 2-aminopropyltriethyoxysilane (APTES) reacted with the Si–O bonds to functionalize the surface with amine groups. ,, An organic linker such as formaldehyde can then be used to attach the polyacrylamide to the surface (i.e., the amides within the polyacrylamide would attach via the organic linker to the amines on the rock surface).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon ideally aims to selectively reduce the water permeability, while causing a minimal effect on the oil/gas permeability. The polymer adsorption on the rock pore walls is considered to be the underlying reason for this phenomenon [ 58 , 59 , 60 ]. Besides polymer adsorption, several mechanisms that contribute to polymer selectivity, including swelling/shrinking [ 61 ] fluid partitioning [ 62 ], lubrication, and steric and wettability effects [ 63 ], have been discussed and debated among scholars.…”
Section: Polymer Systemsmentioning
confidence: 99%
“…Excessive water production is a major challenge in the oil and gas industry as water production can subsequently cause a significant reduction in hydrocarbon productivity and increase the operational costs related to surface water treatment and handling. , Three different types of methods (i.e., chemical, mechanical, and biological) can be applied to regulate or decrease water production. ,,,, This review will focus on chemical treatments which have been extensively utilized to reduce water production. One class of chemical materials that have received widespread attention, due to their potential performance, low cost, and ease of implementation, , are relative permeability modifiers (RPMs) that can selectively reduce the permeability to water while ideally having minimal effect on oil/gas permeability.…”
Section: Introductionmentioning
confidence: 99%